Biofortified millets to alleviate micronutrient malnourishment - Hariprasanna, K (Indian Farming, 2023)
In the 2022 Global Hunger Index, India ranks 107 out of the 121 countries and the severity of hunger is classified as ‘serious’. The proportion of undernourished in the country is 16.3% (2019–21), which amounts to about 224 million people; majority of whom are women and children. Malnutrition and the resultant stunting, wasting, and nutritional deficiencies are prevalent among women and children. The bane of child and maternal malnutrition is responsible for 15% of India’s total disease burden. The Government of India’s POSHAN Abhiyaan or National Nutrition Mission is a flagship programme to improve nutritional outcomes for children, pregnant women and lactating mothers, and to ensure a malnutrition free India. In this regard, development of biofortified millet seems to be a convincing solution which has been discussed in this article.